연구 및 진료에서의 이해상충 - 신지훈; Ji Hoon Shin (Journal of the Korean Society of Radiology, 2022)
Recently, doctors and researchers are establishing relationships with interested parties from companies, research institutes, health care institutions, and academic journals, instead of conducting independent medical care or research work. They may have multiple interests as an advisor or a shareholder in the relevant company. Such a situation can foster a conflict of interest when their interests influence one's decision or judgment. Conflict of interest is an extremely important issue because it can infringe the integrity of research, endanger subjects or patients, pose a risk to the public, and deteriorate public perception of science. This brief review explores the definition, examples, and solutions to conflict of interest. 최근 의사들이나 연구자들은 진료나 연구에서 독자적으로 수행하기보다는, 회사, 연구기관, 보건의료기관, 및 학술 저널의 관련인들과 관계를 맺게 된다, 혹은 그들이 관련 회사에서의 자문 및 주주 참여 등과 같은 다중적 이해관계(multiple interests)를 가지기도 한다. 그러한 이해관계가 연구자의 의사결정에 지대한 영향을 미치는 경우 이해상충이 발생할 수 있다. 이해상충은 연구 진실성을 침해하여 피험자나 환자를 위험에 빠뜨리기도 하고 공공에 대한 위험을 초래할 수 있고 과학에 대한 대중의 인식을 악화시킬 수도 있기에 매우 중요한 문제라고 할 수 있다. 이 종설에서는 이해상충의 개념과 구체적인 사례 및 이에 대한 해법을 살펴보고자 한다.